Logan lucky [videorecording (DVD)] - Soderbergh, Steven, 1963-; Tatum, Channing; Driver, Adam; MacFarlane, Seth, 1973-; Holmes, Katie, 1978-; Swank, Hilary; Craig, Daniel, 1968- (Universal Pictures Home Entertainment, 2017)
Trying to reverse a family curse, brothers Jimmy and Clyde Logan set out to execute an elaborate robbery during the legendary Coca-Cola 600 race at the Charlotte Motor Speedway. In a fun twist, six NASCAR stars pop up in non-driver cameo roles in the film.